ANALISIS PENILAIAN KETANGGUHAN DESA (PKD) DI KABUPATEN BLITAR - Kurniawan, Ficky Adi; Prasetyo, Anggoro Budi; Handayani, Ifiane Nurul; Kurniasari, Surya Heppy; Fandayati, Inggit; Fatah, Zainal; Data, Yulis Bigan (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2025)
Indonesia is a country that has a fairly high potential for natural disasters. Based on disaster risk assessment. Blitar Regency has 10 potential disasters, namely floods, flash floods, extreme weather, high waves and abrasion, earthquakes, forest and land fires, drought, volcanic eruptions, landslides and tsunamis. Assessing village resilience has become an important focus along with increasing efforts to increase village resilience following the high number of disaster events in Indonesia. The disaster resilience assessment aims to produce basic data (baseline) on aspects that influence village resilience. Data collection methods used in village resilience assessment research in Blitar Regency include FGD, observation, and documentation review. Next, the collected data is processed using the application in the BNPB preparedness catalog. The assessment results show that of the 248 villages/sub-districts in Blitar Regency, 170 villages/sub-districts are in the pratama category with a score index of <58.33, 61 villages/sub-districts are in the intermediate category with a score index of 58.33 - 83.33 and 17 villages/sub-districts are in the main category with a score index > 83.33. There are around 17 priority threats chosen by villages/sub-districts in Blitar Regency.